Pengembangan Karir Memediasi Person-Job Fit, Kepuasan Kerja Terhadap Komitmen Kerja Pada Anggota Pasmar 3 - Wimar Ariantanto; Ignatius Soni Kurniawan; Nala Tri Kusuma (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2026)
Background - Human resources are a strategic asset for organizations in achieving long-term goals, including in military organizations that demand discipline, loyalty, and a high level of work commitment. Work commitment is a crucial factor because it reflects an individual's psychological attachment to their work and willingness to maintain membership in the organization. High work commitment is believed to improve organizational stability, individual performance, and the overall sustainability of the institution. Aim – This study aims to analyze the influence of person–job fit and job satisfaction on work commitment, with career development as a mediating variable among members of Pasmar (Marine Corps) 3. Design/Methodology/Approach - This study used a quantitative approach with a survey method. Data collection was conducted by distributing questionnaires to all members of Pasmar 3 using a census technique, thus serving as the entire population sample. The number of respondents in this study was 110. Data were analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) with the assistance of SmartPLS software. Findings - The results of the study indicate that: (1) person–job fit has a positive and significant effect on career development; (2) job satisfaction has a positive and significant effect on career development; (3) person–job fit has a positive and significant effect on work commitment; and (4) job satisfaction has a positive and significant effect on work commitment. However, (5) career development does not have a significant effect on work commitment, and (6) career development is unable to mediate the relationship between person–job fit and job satisfaction on work commitment. Conclusion - Person-job fit and job satisfaction play a dominant role in increasing work commitment, while career development has not been proven to act as a mediating variable in this relationship. Research Implications - This research provides practical implications for organizations, particularly military institutions, that increasing member work commitment is more effective through improving individual job fit and job satisfaction, rather than solely focusing on a formal career development system. Limitations - A limitation of this research is that the research was conducted only in one military unit, namely Pasmar 3, so the results cannot be generalized to other organizations. Furthermore, this research used a cross-sectional design, which only describes conditions within a specific time period.